Efficacy and Safety of Recombinant Activated Factor VII versus Activated Prothrombin Complex Concentrate for Bleeding Control in Acquired Haemophilia A: A Systematic Review and Meta-Analysis - I Made Bayu Indratama; I Wayan Losen Adnyana (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Acquired haemophilia A is a rare autoimmune coagulopathy with mortality of 3.3–22 per cent, in which uncontrolled haemorrhage is the principal cause of early death. Guidelines endorse both recombinant activated factor VII (rFVIIa) and activated prothrombin complex concentrate (aPCC) as first-line bypassing therapy without preference, yet their comparative efficacy has never been quantified by meta-analysis. Objective: To estimate the pooled comparative effect of rFVIIa versus aPCC on bleeding control in adults with acquired haemophilia A, and to assess heterogeneity and thromboembolic safety. Methods: Following PRISMA 2020, three databases were searched (1 May 2026) for cohort, registry, and comparative studies of adults treated with rFVIIa or aPCC. Bleeding-control proportions per arm were pooled as Hedges g under random-effects models, with risk ratio and risk difference as co-primary metrics. Risk of bias used a modified Newcastle–Ottawa Scale; certainty followed GRADE. Results: Ten studies were reviewed and nine meta-analysed (rFVIIa n = 531; aPCC n = 385). Bleeding control occurred in 89.3 per cent (474/531) with rFVIIa and 89.1 per cent (343/385) with aPCC. Pooled Hedges g was 0.026 (95 per cent CI −0.232 to +0.285; p = 0.84), risk ratio 1.00 (0.95–1.06), and risk difference +0.18 percentage points. Heterogeneity was low (I² = 5.8 per cent); findings were robust in sensitivity and subgroup analyses, with low certainty. Conclusion: rFVIIa and aPCC produced clinically equivalent bleeding-control rates in adults with acquired haemophilia A. Agent selection should be guided by availability, acquisition cost, and individual safety profile rather than presumed efficacy.